Structural and magnetic properties of multilayered TiO2/FM/ TiO2/FM/CoFe2O4 (FM: Fe or Py) films grown by pulsed laser deposition - Saccone, Fabio Daniel (2013)
Two types of multilayered thin films of structure TiO2/FM/ TiO2/FM/CoFe2O4 with FM = Fe or Py were grown by means of the pulsed layer deposition technique with a total thickness of less than 350 nm. Their structural properties were analyzed by X-ray diffraction and the Fe K-edge absorption was measured by X-ray fluorescence in grazing incidence geometry. By means of near edge absorption X-ray spectroscopy (XANES), we retrieved information about the octahedral Fe+3 environment within the cobalt ferrite (CoFe2O4) films as well as the role of titanium oxide (TiO2) as a good protective layer for these multilayered systems. The bulk magnetic properties of both samples exhibit certain similarities: at 10 K, the coercive field of their hysteresis loops is enhanced to approximately 1 T, with an intermediate magnetization drop occurring at approximately 2000 Oe reverse field strength, indicating the separated magnetization reversal behavior of pinned and unpinned grains within the FM layers. In contrast to this low temperature field dependence, the collective magnetic behavior is gradual upon field inversion when hysteresis loops are measured at or near room temperature. By using the FORC diagram technique at room temperature, we investigated this gradual transition in more detail and identified clear differences in between the two FM layer materials.